Senior Health Clinic for 75-year-old home-dwelling Finns - study design, clinic protocol and non-response analysis - Salminen Marika; Stenholm Sari; Koskenniemi Jaana; Korhonen Päivi; Pitkänen Tiina; Viikari Paula; Wuorela Maarit; Viitanen Matti; Viikari Laura (BMC, 2025)
Background
In the Finnish policy on older people preventive activities, which maintain functional capacity and independent living, are emphasized. The Turku Senior Health Clinic, aimed at maintaining independent coping of all home-dwelling 75-year-old citizens in the city of Turku, was founded in the beginning of 2020. The aim of this paper is to describe design and protocol of the Turku Senior Health Clinic Study (TSHeC) and provide results of the non-response analysis.
Methods
The non-response analysis used data from 1296 participants (71% of those eligible) and 164 non-participants of the study. Sociodemographic, health status, psychosocial and physical functional ability indicators were included in the analysis. Participants and non-participants were also compared in respect to their neighborhood socioeconomic disadvantage. Differences between participants and non-participants were tested using the Chi squared or Fisher´s exact test for categorical variables and t-test for continuous variable.
Results
The proportions of women (43% vs. 61%) and of those with only satisfying, poor or very poor self-rated financial status (38% vs. 49%) were significantly lower in non-participants than in participants. Comparison of the non-participants and participants in respect to their neighborhood socioeconomic disadvantage showed no differences. The prevalence of hypertension (66% vs. 54%), chronic lung disease (20% vs. 11%), and kidney failure (6% vs. 3%) were higher among non-participants compared to participants. Feelings of loneliness were less frequent among non-participants (14%) compared to participants (32%). The proportions of those using assistive mobility devices (18% vs. 8%) as well as those having previous falls (12% vs. 5%) were higher in non-participants than in participants.
Conclusions
The participation rate of TSHeC was high. No neighborhood differences in participation were found. Health status and physical functioning of non-participants seemed to be slightly worse than those of the participants, and more women than men participated. These differences may weaken the generalizability of the findings of the study. The differences have to be taken into account when recommendation for the content and implementation of preventive nurse-managed health clinic in primary health care in Finland is going to be given.